Call of the wild [videorecording (DVD)] - London, Jack, 1876-1916; Wellman, William A., 1937-; Gable, Clark, 1901-1960; Young, Loretta, 1913-2000; Oakie, Jack, 1903-1978 (Twentieth Century Fox, 2006)
Jack Thornton is an adventurer who travels the Yukon in search of gold. Buck is a sled dog with the strength of his part-wolf ancestry. The pair help a woman find her lost husband in the wild.